Evidence for adaptation of porcine Toll-like receptors - Darfour-Oduro, Kwame A. (Immunogenetics, 2015)
Naturally endemic infectious diseases provide selective pressures for pig populations. Toll-like receptors (TLRs) represent the first line of immune defense against pathogens and are likely to play a crucial adaptive role for pig populations. This study was done to determine whether wild and domestic pig populations representing diverse global environments demonstrate local TLR adaptation. The genomic sequence encoding the ectodomain, responsible for interacting with pathogen ligands of bacterial (TLR1, TLR2 and TLR6) and viral (TLR3, TLR7 and TLR8) receptors, was obtained. Mitochondrial D-loop region sequences were obtained and a phylogenetic analysis using these sequences revealed a clear separation of animals into Asian (n = 27) and European (n = 40) clades. The TLR sequences were then analyzed for population-specific positive selection signatures within wild boars and domesticated pig populations derived from Asian and European clades. Using within-population and between-population tests for positive selection, a TLR2-derived variant 376A (126Thr), estimated to have arisen in 163,000 years ago with a frequency of 83.33 % within European wild boars, 98.00 % within domestic pig breeds of European origin, 40.00 % within Asian wild boars, and 11.36 % within Asian domestic pigs, was identified to be under positive selection in pigs of European origin. The variant is located within the N terminal domain of the TLR2 protein 3D crystal structure and could affect ligand binding. This study suggests the TLR2 gene contributing to responses to bacterial pathogens has been crucial in adaptation of pigs to pathogens. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00251-015-0892-8) contains supplementary material, which is available to authorized users.